Peningkatan Produktivitas Pakan Ternak Itik Kelompok Usaha Bersama di Magelang - Dewi, Rany Puspita; Trisma Jaya Saputra; Mario Ammar Rasyid (Warta LPM, 2023)
The Joint Business Group “Makmur Abadi” is situated around 0.5 km from Tidar University, is focused in duck farming. The processing of animal feed, in this case the pounding of egg shells as the main raw material, is still done manually with a limited capacity using a pestle and mortar. It causes the size of the feed produced is not uniform. The aim of this activity was to improve the capacity and quality of animal feed produced by partners. The ctivities was done in two phases. The first stage was started with data collection and discussions with partners. The second stage was comtinued with coordination to develop the stage of solving the problem through the application of an egg shell flour machine. Measuring the effectiveness of animal feed production was carried out by quantifying the capacity and quality of the animal feed generated and measuring the increase in residents' knowledge pre and post the implementation of the machine. The primary output of this activity was an egg shell flour machine which is made with a capacity of 20 kg/hour, consumes 367.75 watts of power, and is equipped with various filter sizes that can be customized to the need of partners. The use of an egg shell flour machine was able to increase production capacity from only 10 kg/day to 20 kg/hour with a more uniform size that is easily digested by livestock. This activity was also able to increase public awareness up to 90%.